Correction: Metabolite changes during developmental transitions in Adonis amurensis Regel et Radde flowers: Insights from HPLC-MS analysis. - Zhu Xingzun; Wang Hongtao (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0313337.].